Antiviral treatment of COVID-19 - Andina, Andina; Sugiarto, Sugiarto; Pamungkas, Pamungkas (International Medical Journal Corp. Ltd, 2024)
Background: The literature on antiviral treatments for COVID-19 reflects a rapidly evolving field, characterized by a diversity of therapeutic strategies and ongoing clinical investigations. The collaborative efforts of various institutions have been pivotal in identifying effective treatment options, as evidenced by the RECOVERY trial's findings on dexamethasone and remdesivir's efficacy (Sarkar et al., 2020). The urgency for effective treatments is underscored by the ongoing transmission of the virus and the emergence of new variants, necessitating a comprehensive evaluation of available antiviral agents. Literature Review: Favipiravir has emerged as a significant candidate for treating mild to moderate COVID-19 cases, with systematic reviews and meta-analyses indicating its clinical efficacy (Hassanipour et al., 2021). The comparative analysis of favipiravir and remdesivir highlights their mechanisms of action, reinforcing the need for continued exploration of these and other antiviral options (Andrei Negru et al., 2022). Furthermore, molnupiravir has gained attention for its promising pharmacokinetics and clinical trial results, demonstrating its potential in the antiviral arsenal against COVID-19 (Khiali et al., 2022). The landscape of antiviral therapies is further enriched by a comprehensive review of small-molecular therapeutics, emphasizing the need for novel strategies to address the challenges posed by emerging variants (Zhong et al., 2022). The repurposing of established drugs with known safety profiles remains a critical area of focus, as highlighted by the analysis of various antiviral agents, including remdesivir and favipiravir (Sahin et al., 2022).. Conclusion: In conclusion, the body of literature reflects significant advancements in the antiviral treatment of COVID-19 while highlighting the complexities and challenges that remain. The continuous evaluation and adaptation of therapeutic strategies are essential to effectively combat the evolving landscape of COVID-19 and its associated variants.